PERENCANAAN STRUKTUR BETON BERTULANG GEDUNG PERPUSTAKAAN PUBLIK KOTA PONTIANAK: PERENCANAAN STRUKTUR BETON BERTULANG GEDUNG PERPUSTAKAAN PUBLIK KOTA PONTIANAK - Setiawan, Ivan; zuraida, ida; Sergius, sergius; wiidhiyastuti, rahayu (RETENSI, 2022)
Pontianak as the capital city of West Kalimantan province is a city where there are many people with various professions such as: students, teachers, doctors, employees, students, entrepreneurs and others. From these various professions, it is necessary to have a source of knowledge or information for the general public so that they can always be responsive to advances in technology, science, social life, political life, and culture. There is only one public library in Pontianak City, making it easier for students and students to access information that is easy, cheap, fast, and precise. For the construction planning, a reinforced concrete structure consisting of 4 floors is used with concrete quality specifications (fc')25, 28, 30 MPa, and steel quality 420 (fy) calculated based on the Indonesian National Standard (SNI), namely SNI 03-2847-2013 and using the SAP2000 application for the calculation of internal forces, so that a plan drawing can be made according to the calculation results obtained. The calculation results also obtained reinforcement for the 1st floor to the roof not with a thickness of 12 cm for the floor plate, 10 cm thick for the roof not, the beam used was 25 cm x 45 cm, the column used was 35 cm x 35 cm, the foundation used is a type of pile foundation, with a pile size of 35 cm x 35 cm as many as 8 pieces, the dimensions of the pile cap used are 210 cm x 210 cm with a height of 50 cm.